Case report: A case of perineal prolapse of giant uterine fibroids complicated by multiple pulmonary embolisms and deep venous thrombosis - Dong, Shixiang; Sun, Xin; Yu, Fengsheng; Wang, Wenjie; Zhang, Li; Wang, Yankui; Yu, Xiao (Frontiers in Oncology, 2024)
A 43-year-old woman with a history of uterine fibroids, anemia, and deep vein thrombosis presented with a chief symptom of prolapse of tumor from the perineum, complicated by infection. The case was further complicated by bilateral pulmonary multiple embolism, deep vein thrombosis, acute cardiac insufficiency, acute renal insufficiency, and shock. The patient was treated with preoperative placement of an inferior vena cava filter, open hysterectomy, and perioperative anticoagulation with low-molecular-weight heparin. She smoothly navigated the perioperative period and recovered completely.